Eruptive dynamics are common in managed mammal populations. Issue 12 (6th October 2020) - Duncan, Richard P.; Dexter, Nick; Wayne, Adrian; Hone, Jim
Abstract: Successful conservation management is often based on the principle that small or declining populations can recover if we identify and remove the factors that caused them to decline in the first place. But what form will that recovery take? Theory tells us that when a strong limiting factor is removed, a population should increase in size to where it becomes limited by some other factor. However, if the subsequent limitation involves feedbacks between the density of a consumer and its resource, there is potential for the consumer population to undergo substantial fluctuations in size that we would characterize as boom‐bust or eruptive dynamics. We analysed long‐term (7.6–29 yr) data documenting changes in the abundance of 169 populations of 20 mammal species released from a strong limiting factor (fox predation) in Australia. We show that many populations (44) exhibited eruptive dynamics, with exponential increase to a peak and subsequent population decline. Of 51 populations showing eruptive dynamics (the Australian populations plus seven translocated ungulate populations), the time taken for erupting populations to reach a peak before declining was related negatively to the intrinsic rate of population growth and positively to body mass, such that larger‐bodied species with slow rates of population growth had a longer period of population increase before declining. Our results suggest that a substantial proportion of populations recovering after removal of a threatening process are likely to exhibit eruptive dynamics, and that managers of recovering or translocated populations should anticipate this outcome in conservation planning.